Psychotherapy, Counselling, Personal Development: Array - Mocanu, Lacramioara (Didactica Danubiensis, 2022)
Psychology has recently taken on a social and even political role. Psychotherapy seems to be replacing medicine itself and that is why its social role is becoming increasingly important. Counseling is based on the improving techniques of psychotherapy and personal development seems more like a trend. We make a distinction between psychotherapy, counselling, personal development, define them and propose their insertion in today’s curriculum.